From “rooted out” to “rootless”: Images of Emigration in Lithuanian Drama - Mažeikienė, Rūta (Nordic Theatre Studies, 2015)
Since the early 1990s, when the Iron Curtain was lifted after over fifty years of Soviet occupation, approximately 800 000 citizens of Lithuania have emigrated, leaving a population of less than three million. This article addresses the phe- nomenon of emigration from Lithuania and analyzes how the issue of emigration and the experiences of the emigrants are reflected in Lithuanian drama. In the first part of the article, two plays – Without Conscience (Be sumnenės arba kaip ant svieto einasi) by Antanas Turskis and America in the Bathhouse (Amerika pirtyje) by Keturakis – will be analysed focusing on how the late nineteenth century plays shaped a critical attitude towards emigration, deconstructed the myth of the foreign land of gold and proposed a romantic image of the motherland as one’s native soil where one needs to return. The second part of the article analyses the plays Goodbye, My Love (Antoškos Kartoškos) by Marius Macevičius and Expulsion (Išvarymas) by Marius Ivaškevičius and points out how reflection on the contemporary experience of emigration helps to explore deeper problems of post-Soviet society and the individual such as a sense of placelessness and fragmented identity. A comparative analysis of these texts makes it possible to analyse the dynamics of the different conceptions of emigration, emigrant’s identity and self-perception as well as their artistic representations.